Challenges in Implementing PSAK 409 in the Financial Statements of Zakat Management Institutions - Suriyati, Andi; Mubarok, Moh Husni; Azwari, Peny Cahaya (The Future of Education Journal, 2025)
PSAK 409 on Amil Financial Reporting is an accounting standard designed to improve transparency, accountability, and the quality of financial statements in Lembaga Amil Zakat (LAZ). However, its implementation still faces various challenges, particularly in institutions with limited resource capacity. This article discusses the main obstacles encountered by LAZ in applying PSAK 409, including limited technical understanding of human resources, uneven availability of adequate accounting information systems, difficulties in recording zakat-infaq-sedekah funds according to standard classifications, and lack of continuous training. In addition, this article examines how regulatory factors, institutional size, and technological readiness also affect successful implementation. Identifying these challenges is expected to serve as a basis for developing strategies to enhance standard compliance and formulate supporting policies so that LAZ financial reporting can become more transparent and reliable.